Influence of microstructural defects on the thermal conductivity of GaN: A molecular dynamics study. Issue 8 (25th February 2013) - Spiteri, David; Pomeroy, James W.; Kuball, Martin
Abstract The lattice thermal conductivity is known to depend on crystal quality, but the reduction in thermal conductivity due to specific defects is presently unclear. Molecular dynamics simulations were used to investigate the impact of microstructural defects on the thermal conductivity of gallium nitride. The conductivity of a finite crystal was reduced to (39 ± 4)% by a screw dislocation density of 2.0 × 1013 cm−2 and to (51 ± 4)% by an edge dislocation of similar density, illustrating that the type of dislocation is important for thermal conductivity. The effect of stacking faults on thermal conductivity was also investigated.